Answer:
I'll go over the first two problems and you'll probably be able to do the rest on your own.
1.)
g(a) = 4a - 2
h(a) = -3a² - 2
Find (g○h)(a)
What (g○h)(x) mean is g( f(x) ). In this case, we have
(g○h)(a) so it's the same as g( f(a) ). All you do for this is plug in f(a) into every a that you see in g(a).
(g○h)(a) = g( f(a) )
(g○h)(a) = g( -3a² - 2 )
(g○h)(a) = 4(-3a² - 2) - 2
(g○h)(a) = -12a² - 10
2.)
g(n) = 2n - 3
f(n) = 2n³ + 2n²
(g○f)(n) = g( f(n) )
(g○f)(n) = g( 2n³ + 2n² )
(g○f)(n) = 2(2n³ + 2n²) - 3
(g○f)(n) = 4n³ + 4n² - 3